A matriz gesto-sinais e a multimodalidade no processo de reconto de narrativas por crianças surdas e codas - Sousa, Francisco Ebson Gomes (2025)
This thesis investigates the process of retelling narratives by deaf children and codas (Children of Deaf Adults). It uses a multimodal approach that encompasses language beyond the spoken word, incorporating signs, gestures, facial expressions, gaze, use of space, and other semiotic resources that shape the communicative complexity of these children. Within the field of language acquisition, the research begins with the central issue of how deaf children and codas, in the process of language acquisition, retell narratives. It seeks to understand the relationships established between signs and the gesture-speech matrix traditionally described in the literature, proposing the gesture-sign matrix as a contribution. The general objective was to understand the functioning of this gesture-sign matrix in the retellings produced in dialogic contexts by deaf children and codas, being operationalized by the specific objectives of (I) understanding the importance of retelling for the linguistic development of these children, (II) investigating the functions of gestures in the retelling of multimodal narratives and (III) observing the multimodal aspects triggered by them when retelling stories. The research has a qualitative and descriptive character, anchored in the analysis of video recordings of retellings carried out by deaf children and codas, in which the articulation between different multimodal resources was observed, such as Libras (Brazilian Sign Language) signs, iconic gestures, pantomimes, facial expressions, classifiers and the strategic use of discursive space. Theoretically based on prominent authors in the studies of multimodality, gestures and language acquisition, such as: Kendon (2000, 2009), McNeill (1992, 2000, 2013), Tomasello (2009, 2021), Goldin-Meadow (2003, 2009), Quadros (1997, 2003, 2006), Cavalcante (1994, 2018, 2019), McCleary and Viotti (2011), the study also dialogues with national and international perspectives that recognize gestures not only as complements to speech or signaling, but as constitutive elements of human language. The results show that, in the retelling process, deaf and coda children mobilize distinct multimodal repertoires, anchored in diverse linguistic experiences and different modalities, whether oral-auditory or gestural-visual, constructing rich and visually complex narratives. The main finding, the proposition of the gesture-sign matrix, expands the classic gesture-speech matrix model, considering the specificities of visual-spatial languages, such as Libras. This gesture-sign matrix reveals that linguistic signs, iconic gestures, pantomimes, and other gestural resources co-occur in an integrated and dynamic manner in the act of enunciation, functioning as co-participating elements in the production of meaning. Furthermore, it was found that retelling narratives constitutes a relevant practice for linguistic and cognitive development, fostering the construction of discursive memory, identity, and cultural belonging, especially in the case of deaf children. The central contribution of this research, therefore, lies in the systematization of the gesture-sign matrix as an analytical tool for studying language acquisition in children who use sign languages, fostering a more sensitive perspective on the multimodal specificities of these languages. This proposal broadens the field of research on multimodality and language acquisition, particularly regarding the need to consider the integration of signs and gestures in the analysis of children's linguistic development in bilingual and bimodal contexts.